Effect of rice husk ash fineness on porosity and hydration reaction of blended cement paste. (1st August 2015) - Xu, Weiting; Lo, Yiu Tommy; Ouyang, Dong; Memon, Sharzim Ali; Xing, Feng; Wang, Weilun; Yuan, Xiongzhou
Highlights: We investigate the grinding effect on the pozzolanic reactivity of RHA. We study the mechanical, hydration and porosity properties of RHA paste. The strength, hydration reaction and porosity of RHA paste were studied. Paste with 30-min grinding RHA performs best in strength, hydration and porosity. Abstract: An experimental investigation on the effect of grinding fineness of rice husk ash (RHA) on the mechanical, hydration and porosity properties of RHA blended paste was launched. Locally produced RHA with six different grinding durations of 5, 10, 30, 60, 90 and 120 min corresponding to mean particle size of 8.61, 8.15, 5.45, 6.25, 6.38 and 6.95 μm, respectively, were used in this study. The physical and chemical properties of the ground RHAs were determined and results show that variations in chemical composition of RHAs with different grinding fineness are small. The pastes with water binder ration of 0.4 and cement substitution of 10% by ground RHAs were tested. Comparisons between pastes with SF, and control paste (only with ordinary Portland cement) were also presented. Mechanical properties, hydration reaction and porosity of paste were investigated by compressive strength, thermogravimetric analysis (TGA) and environment scanning electron microscope (ESEM) plus Image Pro Plus software analysis, respectively. Results show that incorporation of 30-min grinding RHA exhibits a strong, high hydration and low porosity paste due to the better dispersion, filling effect and pozzolanic activity.